IPEX due to an exon 7 skipping FOXP3 mutation with autoimmune diabetes mellitus cured by selective TReg cell engraftment - Magg, Thomas (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2018 Elsevier Inc. All rights reserved.